Presidente Aristeu Borges de Aguiar, de positiva unanimidade a expectativas frustradas. a política e a economia capixabas durante os anos 1928 a 1930. - Wanick, Flavio Calmon (2007)
This research places the "Capixaba" politics and economy in evidence, during the years 1928 to 1930 when the presidency of the State was occupied by the teacher and lawyer, Aristeu Borges de Aguiar. Analyse how the national political dissidence, which occurred in the cradle of the dominant oligarchy, in view of the choice of Julio Prestes' name as a candidate to be Washington Luís' successor (1926 to 1930), agitated the "espírito-santenses" political relations which at the time were relatively calm. It demonstrates the speed that the economical crises of 1929 affected the capixabas' finances. Verify how President Aristeu, after obtaining unanimously in favour of his name, lost his popularity during the course of his mandate in his State. It identifies the existence of one strong approach economic and political in these years between the State of the Espirito Santo and of São Paulo.